THE IMPACT OF THE POLICY OF NATIONAL COMMUNITY EMPOWERMENT PROGRAM SELF-SUFFICIENT RURAL COMMUNITY LIVELIHOOD IMPROVEMENT IN THE VILLAGE OF PASLATEN SUBDISTRICT OF REMBOKEN - DJAMI, FADILA; Laloma, alden; Londa, Very (Sam Ratulangi University, 2017)
Abstract : Government policies to improve the livelihood of the community improvement in povertyreduction to date continues to be carried out, even a variety of programs have been proposed by theGovernment to reduce the gap between the rich and the poor. In connection with the program, theGovernment of Indonesia mencenangkan National Community Empowerment Program Self-sustainingRural with inside are program development and infrastructure programs and Save Loan women whobecome the focus in this research.Aiming to find out the impact of the policy of National Community Empowerment Program SelfsufficientRural Community Livelihood improvement in the village of Paslaten sub-district of Remboken.The researchers used a qualitative method, infoman in this study amounted to 9 people. Instruments anddata collection Techniques are in use are guidelines for interviews and help with interviews and observation.Keyword: impact pnpm, standard of living